Evaluating Surgical Outcomes in Vulnerable Populations Infection Risk Following Wisdom Tooth Extraction in Patients with Developmental Disabilities - Syeda Arzoo Azeem, Wajida Jawed, Nadia Chughtai, Faizah Hassan, Syed Ashar, Syed Fahad Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Wisdom tooth extraction is a common oral surgical procedure, often associated with postoperative infections. Patients with developmental disabilities (DDs) face increased risks due to compromised oral hygiene, communication barriers, and the frequent need for general anesthesia. Objective: This study aimed to evaluate the incidence and risk factors of postoperative infections following third molar extraction in individuals with DDs. Methods: The study was a prospective observational study carried out between March 2022 and March 2023 in three tertiary hospitals in Karachi, Pakistan. One hundred and thirty patients aged 12 years and above with DDs, such as intellectual disability, autism spectrum disorder, and cerebral palsy, underwent the extraction of wisdom teeth. Statistical analysis of data on type of anesthesia, oral hygiene, complexity of surgery and outcome of infections were made. Results: The incidence of postoperative infection was 21 (16.2%). Infection was significantly related to poor oral hygiene (p = 0.003), general anesthesia (p = 0.041), and removal of impacted third molars (p = 0.017). There was a non-significant protective trend with prophylactic antibiotics (p = 0.087). Infections were generally localized and treated conservatively without any significant complications and readmissions. Conclusion: DDs patients face a greater risk of infection after the extraction of third molars, especially in cases with poor oral hygiene and high surgical difficulty. Personalized care and specific perioperative interventions are needed to enhance the outcomes of this at-risk population. Keywords: wisdom tooth extraction, developmental disabilities, postoperative infection, oral surgery outcomes, general anesthesia